2007
DOI: 10.1002/cphc.200600737
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Orbit Ab Initio Investigation of the Ultraviolet Photolysis of Diiodomethane

Abstract: The UV photodissociation (<5 eV) of diiodomethane (CH(2)I(2)) is investigated by spin-orbit ab initio calculations. The experimentally observed photodissociation channels in the gas and condensed phases are clearly assigned by multi-state second-order multiconfigurational perturbation theory in conjunction with spin-orbit interaction through complete active space-state interaction potential energy curves. The calculated results indicate that the fast dissociations of the first two singlet states of CH(2)I(2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 69 publications
2
20
0
Order By: Relevance
“…16,17 The electronic structure of CH2I2 has been described qualitatively using an exciton model 8 as well as theoretically using ab initio calculations that include effects of spin-orbit coupling and show that excited states with heavily mixed singlet and triplet character are responsible for the absorption spectrum. 18,19 Photolysis of gas phase CH2I2 in the near-UV leads to energy being partitioned predominantly into internal excitation of the iodomethyl (CH2I) radical rather than translation, with fT reduced to ~0.2. 8,18,[20][21][22][23][24][25] The I* yield is effectively zero following excitation at longer wavelengths, but steadily increases to almost 0.5 at 248 nm.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The electronic structure of CH2I2 has been described qualitatively using an exciton model 8 as well as theoretically using ab initio calculations that include effects of spin-orbit coupling and show that excited states with heavily mixed singlet and triplet character are responsible for the absorption spectrum. 18,19 Photolysis of gas phase CH2I2 in the near-UV leads to energy being partitioned predominantly into internal excitation of the iodomethyl (CH2I) radical rather than translation, with fT reduced to ~0.2. 8,18,[20][21][22][23][24][25] The I* yield is effectively zero following excitation at longer wavelengths, but steadily increases to almost 0.5 at 248 nm.…”
Section: Introductionmentioning
confidence: 99%
“…These products are predicted to have transitions in the visible or near UV with very large oscillator strength (∼0.5). 17,41,43,44 Femtosecond transient absorption (TA) measurements in acetonitrile 25,45 and picosecond time resolved resonance Raman (TR 3 ) experiments in cyclohexane 40 have shown that A band excitation at 266 nm in solution results in formation of the iso-CH 2 Br-I photoproduct. The visible spectrum of the photoproduct is similar to that observed in low temperature matrix experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The only earlier report of PECs of excited states is by Ya-Jun Liu et al 27 who have investigated UV photolysis pathways using spin-orbit coupled multistate complete active space second order perturbation method and calculated potential energy curves for the first four singlet and triplet excited states. The present work is mainly concerned with explanation of spectral features observed in the UV photoabsorption spectrum.…”
Section: Valence Excited Statesmentioning
confidence: 99%
“…Dipole forbidden states and states with very low oscillator strength are omitted from this table, as also states of mixed nature which are already included in Rydberg assignments. The first six singlet excited states including the forbidden A 2 state have been calculated earlier using the complete active space second order perturbation method (CASPT2) by Liu et al 27 Their results are shown in parentheses in Table VIII for comparison. It may be seen that excitation energies are in overall good agreement except for reordering of some of the states.…”
Section: Valence Excited Statesmentioning
confidence: 99%
See 1 more Smart Citation